2014
DOI: 10.1111/jph.12215
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coat Protein of Peanut stunt virus Subgroup II Isolates from Alfalfa Fields in West Iran

Abstract: Alfalfa fields in three western provinces of Iran were surveyed for Peanut stunt virus (PSV) during 2011 and 2012. Forty‐seven of 115 samples tested (41%) were infected with PSV. Phylogenetic analysis using coat protein (CP) gene sequences showed that the Iranian isolates belong to the subgroup II of PSV. Pairwise identity analysis revealed four groups representing four phylogenetic subgroups. PSV strains in subgroups III and IV are closely related to each other, as supported by the lowest nucleotide diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The CP gene of Iranian PSV isolates from the current study and those of four previously reported Iranian isolates by Pourrahim and Farzadfar [30] (Acc. Nos.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The CP gene of Iranian PSV isolates from the current study and those of four previously reported Iranian isolates by Pourrahim and Farzadfar [30] (Acc. Nos.…”
Section: Discussionsupporting
confidence: 62%
“…According to previously established groupings, the 20 Iranian isolates from this study were all clustered in subgroup II. Five previously characterized Iranian PSV isolates [30] also were grouped in this subgroup. Based on pairwise identities ([96% identity) coupled with maximum likelihood phylogenetic, five isolates from the current study together with four previously characterized Iranian isolates (Acc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peanut stunt virus (PSV) is a pathogen of plants, especially legumes, which belongs to genus Cucumovirus [ 1 , 2 , 3 , 4 , 5 ]. The PSV genome consists of three (+)single-stranded RNAs and five open reading frames (ORFs) encoding the 1a and 2a components of the viral replicase, the movement protein, the coat protein (CP), and the 2b protein known as a viral silencing suppressor [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…CMV and PSV, used as positive control, were obtained from our previous studies Farzadfar et al 2013;Pourrahim and Farzadfar 2014). Leaf tissue from the symptomatic plants was used to mechanically inoculate appropriate herbaceous indicator plants including species belonging to Amaranthaceae, Chenopodiaceae, Fabaceae, Lamiaceae and Solanaceae families.…”
Section: Introductionmentioning
confidence: 99%